2012
DOI: 10.1111/j.1467-8624.2012.01810.x
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Well‐Being Among Children of Migrant Parents in South‐East Asia

Abstract: There has been little systematic empirical research on the well-being of children in transnational households in South-East Asia—a major sending region for contract migrants. This study uses survey data collected in 2008 from children aged 9, 10, and 11 and their caregivers in Indonesia, the Philippines, and Vietnam (N = 1,498). Results indicate that while children of migrant parents, especially migrant mothers, are less likely to be happy compared to children in nonmigrant households, greater resilience in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
168
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(180 citation statements)
references
References 48 publications
11
168
1
Order By: Relevance
“…Most transnational family studies restrict their focus to children of migrant parents who are in a stable marital relationship (Donato & Duncan, 2011;Jordan & Graham, 2012;Wen & Lin, 2012). In doing so, these studies are able to assess how the parental input in a stable family environment is invested in the health of children in transnational care.…”
Section: Transnational Families and Child Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Most transnational family studies restrict their focus to children of migrant parents who are in a stable marital relationship (Donato & Duncan, 2011;Jordan & Graham, 2012;Wen & Lin, 2012). In doing so, these studies are able to assess how the parental input in a stable family environment is invested in the health of children in transnational care.…”
Section: Transnational Families and Child Healthmentioning
confidence: 99%
“…Although precise numbers of children in transnational care are not available, data show that up to 38 per cent and 21 per cent of Ghanaian and Nigerian children, respectively, excluding orphans, had at least one biological parent who was away in 2008 (GDHS, 2008;NDHS, 2008). For these children, the absence of parents has likely become a common feature of their lives, and scholars are now asking how different contexts of parental absence affect children's wellbeing (Jordan & Graham, 2012;Mazzucato & Schans, 2011) and children's health (Donato & Duncan, 2011;Donato, Kanaiaupuni, & Stainback, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that as compared with their non-left-behind peers, left-behind children were more likely to suffer from a high level of loneliness, life dissatisfaction, and unhappiness (Jia and Tian, 2010;Jordan and Graham, 2012;Su et al, 2013). However, there has been a lack of study exploring the influence of parental absence on children's academic performance among the left-behind children.…”
mentioning
confidence: 90%
“…The above claim is compatible with the fact that the overall impact on children of their parents' migration is both complex and disputed (see sources cited in Lutz and Palenga-Mollenbek 2012;Jordan and Graham 2012 Thanks to remittances, migrants' children-just like other family membersare materially better off than before migration and sometimes better off than children whose parents do not (need to) migrate. The money sent by their migrant parents buys them better food, accommodation, and education, but sometimes also functions to single them out among their peers, and even ostracize them (AAS 2006;Piperno 2007a;Isaksen, Devi, and Hochschild 2008).…”
Section: B Continuity In Care and Children's Moral Rightsmentioning
confidence: 73%